2017
DOI: 10.1123/ijsnem.2016-0228
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Effects of Beetroot Crystals and Sodium Bicarbonate on 4-km Cycling Time Trial Performance

Abstract: When ingested alone, beetroot juice and sodium bicarbonate are ergogenic for high-intensity exercise performance. This study sought to determine the independent and combined effects of these supplements. Eight endurance trained (VO 2 max 65 mL·kg·min -1 ) male cyclists completed four × 4-km time trials (TT) in a doubleblind Latin square design supplementing with beetroot crystals (BC) for 3 days (15 g·day -1 + 15 g 1 h before TT, containing 300 mg nitrate per 15 g), bicarbonate (Bi 0.3 g·kg -1 body mass [BM] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 29 publications
3
39
1
2
Order By: Relevance
“…Discrepancies could be due to timing and subsequent increases in circulating bicarbonate. Mean bicarbonate increases in Gough et al ( 48 ) were +6.5 ± 1.3 mmol·L −1 , which is higher than the approximate +3 mmol·L −1 ( 78 ) and +5 mmol·L −1 ( 79 ) shown 150 and 100 min following supplement ingestion in the other studies. Despite these initial positive results, no data exist directly comparing exercise performed at the moment of peak circulating bicarbonate to a standardized time (e.g., 60 min) following supplementation in the same participants.…”
Section: Potential Influencing Factors On the Efficacy Of Extracellulmentioning
confidence: 55%
“…Discrepancies could be due to timing and subsequent increases in circulating bicarbonate. Mean bicarbonate increases in Gough et al ( 48 ) were +6.5 ± 1.3 mmol·L −1 , which is higher than the approximate +3 mmol·L −1 ( 78 ) and +5 mmol·L −1 ( 79 ) shown 150 and 100 min following supplement ingestion in the other studies. Despite these initial positive results, no data exist directly comparing exercise performed at the moment of peak circulating bicarbonate to a standardized time (e.g., 60 min) following supplementation in the same participants.…”
Section: Potential Influencing Factors On the Efficacy Of Extracellulmentioning
confidence: 55%
“…We terminated our study search in April 2016 but the field of ergogenic supplements continues to evolve. Recently, studies has been published showing no effect on intense endurance performance from both bicarbonate (Callahan et al, 2016) and nitrate (Callahan et al, 2016) supplementation whereas caffeine has resulted in both unchanged (Cordingley et al, 2016) and improved performance (Boyett et al, 2016). A number of the included studies in the current meta-analysis also reported negative findings, so to what extent an actual publication bias toward positive results exits remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The χ 2 test showed a different distribution among the PL (P = 0•002). Rimer et al (73) Rimer et al (2) (72) Lane et al Glaister et al (60) Peeling et al (1) (71) McQuillan et al (8) 67Martin et al (3) (66) Bescós et al (2) (25) Callahan et al (1) (59) Callahan et al Muggeridge et al (2) (69) McQuillan et al (1) (68) Bescós et al (1) (25) Thompson et al (2) Lowings et al (65) Cermak et al (2)…”
Section: Analysis Of the Relationship Between The Performance Level Amentioning
confidence: 99%
“…(2) (21) Cermak et al (1) (21) Nyakayiru et al (1) (50) Wilkerson et al (1) (76) Callahan et al (1) (59) Callahan et al…”
unclassified